2006
DOI: 10.1111/j.1467-6427.2006.00354.x
|View full text |Cite
|
Sign up to set email alerts
|

Trainee perspectives on their family therapy training

Abstract: a Although research into family therapy training is increasing it has so far mostly focused on the process of the teaching and acquisition of certain concepts and skills. In contrast, the experience of training as family therapists has rarely been investigated. This paper reports on the impact of family therapy training at one training institution in the UK on the personal, relational and professional identities of trainees. Six family therapy trainees were interviewed using semi-structured interviews at regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 41 publications
2
33
0
Order By: Relevance
“…The findings in this study are consistent to some degree with results from the prior studies conducted by Nel (2006) and Paris et al (2006). Nel found that trainees reflected on personal relationships, both in the present and the family of origin, but more emphasis was placed on the stresses of training and it's effects on family life as well as the tension involved in balancing work, training, and motherhood.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The findings in this study are consistent to some degree with results from the prior studies conducted by Nel (2006) and Paris et al (2006). Nel found that trainees reflected on personal relationships, both in the present and the family of origin, but more emphasis was placed on the stresses of training and it's effects on family life as well as the tension involved in balancing work, training, and motherhood.…”
Section: Discussionsupporting
confidence: 92%
“…It is also interesting that the majority of the aspects of training listed as responsible for personal development involved trainees actually doing relationships rather than learning family therapy skills. The findings of this study and the two prior studies by Nel (2006) and Paris et al (2006) exemplify a culture of teaching in family therapy that aims to foster relational expertise, not simply the development of technical proficiency in interviewing and intervention.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…A brief search for IPA in this journal revealed no published studies and a similar search in five other top American couple and family therapy research journals found a total of five published articles through the end of 2014 where the authors referred to the use of IPA (e.g. Lloyd & Dallos, 2008;McCandless & Eatough, 2010Nel, 2006). There has been limited mention of it in key texts in the couple and family therapy field (e.g.…”
Section: The Use Of Interpretive Phenomenological Analysis In Couple mentioning
confidence: 99%
“…Research studies by Reay (2003) and Reay et al (2010) highlight the shift -and loss -of identity that occurs when students from working class backgrounds experience a disjuncture between their families' culture and values and those of the higher education setting. Kevern and Webb (2004) found that mature women undertaking nurse education reported negative consequences for their personal relationships; and in Nel's (2006) research, family therapy trainees -mature postgraduates with a range of professional qualifications -described having to re-evaluate their personal and professional identities.…”
Section: Identity Work: Becoming a Social Work Professionalmentioning
confidence: 99%